2022
DOI: 10.3389/phrs.2022.1604583
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Implementation of Remote Delivery Strategies for Non-Communicable Disease Care in Low- and Middle-Income Countries: A Narrative Review

Abstract: Objectives: The COVID-19 pandemic has disrupted health care for non-communicable diseases (NCDs) and necessitated strategies to minimize contact with facilities. We aimed to examine factors influencing implementation of remote (non-facility-based) delivery approaches for people with hypertension and/or diabetes in low- and middle-income countries (LMICs), to inform NCD care delivery during health service disruption, including humanitarian crises.Methods: Our narrative review used a hermeneutic and purposive ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…According to the WHO, telemedicine and patient triage were the most common mitigation strategies used to reduce NCD service disruption in the early days of the pandemic [16]. However, our study re ects the literature around the introduction of telehealth -its success is highly contingent on national infrastructure, smartphone ownership rates, and on internal organisational factors, while clear guidance, training and culturally-congruent communication all support its successful implementation [27]. Our data also highlight the need for guidance for clinicians in the use of telemedicine, in keeping with previous calls for speci c WHO guidance on the development and use of digital health solutions for NCD care [19].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…According to the WHO, telemedicine and patient triage were the most common mitigation strategies used to reduce NCD service disruption in the early days of the pandemic [16]. However, our study re ects the literature around the introduction of telehealth -its success is highly contingent on national infrastructure, smartphone ownership rates, and on internal organisational factors, while clear guidance, training and culturally-congruent communication all support its successful implementation [27]. Our data also highlight the need for guidance for clinicians in the use of telemedicine, in keeping with previous calls for speci c WHO guidance on the development and use of digital health solutions for NCD care [19].…”
Section: Discussionmentioning
confidence: 88%
“…We focussed on the delivery of care for hypertension, type-1 and type-2 diabetes ('DM/HTN', implying care for either or all conditions) as these are the most common NCD types currently addressed by humanitarian organisations [12,26]. These conditions are also established tracer conditions, used globally by WHO for the assessment of services for crisis-affected populations delivered within public, private, and parallel health systems (including the humanitarian or informal sector) [12,27].…”
Section: Methodsmentioning
confidence: 99%
“…This showed that the closer an individual's residence to a community health centre, the easier it was to access medical resources. Access to disease resources was associated with self‐care in patients with T2DM (Favas et al, 2022). Self‐care should be improved by providing multichannel diabetes management resources.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, people living with NCDs were therefore at double risk; rstly, they were at increased risk for developing severe and even fatal COVID-19 because of their underlying condition, and secondly, since their chronic care provision was impeded, they were at risk of developing acute and long term complications. (2,(4)(5)(6)(7).…”
mentioning
confidence: 99%